Full metal jacket [videorecording (DVD)] - Kubrick, Stanley; Modine, Matthew; Baldwin, Adam, 1962-; D'Onofrio, Vincent; Hasford, Gustav (Warner Home Video, 2001)
Vietnam war drama which begins with a depiction of the brutality of Marine Corps training and then shifts to Vietnam, focusing mainly on a group of Marines responding to the Tet Offensive of 1968.